Study of Household Waste Management and Recycling Awareness Between Residential Areas in Kuala Nerang, Kedah, Malaysia - Abdul Halim, Husna; Mohamed Najib, Mohamed Zuhaili; Zainal Abideen, Muzaffar; Basri, Hazlami Fikri; Muda, Khalida (Tecno Scientifica Publishing, 2022)
This paper presents a study on household waste management and recycling awareness. Residential areas are the major sources of solid waste as that is where people live. The waste that is usually disposed of from residential areas includes food waste, plastic waste, paper, glass, tin, and others. The increasing trend in waste generated from homes has become a major concern. This study aimed to assess household waste management and recycling awareness in two residential areas located in Padang Terap District, Kuala Nerang, Kedah, Malaysia. Recently, Padang Terap district showed an increase in waste generated compared to another district, Kedah. An open-ended questionnaire was distributed to approximately 32 respondents, and an interview was conducted to study household waste management and recycling awareness in two residential areas—Taman Jati and Taman Pelangi. The research shows that household waste management to segregate the waste remains a problem, despite most respondents being aware of this issue through different media. Furthermore, the lack of household waste management and recycling programs and facilities by the local authorities caused residents to be reluctant to practice these activities.